DEVELOPING COMPETENCY FRAMEWORKS IN THE CIVIL SERVICE SYSTEM - TAKING THE MINISTRY OF HOME AFFAIRS OF VIETNAM AS A CASE STUDY - Dao, Thuy Thi Thanh (Advances in Social Sciences Research Journal, 2019)
Competency–based human resource management is a management approach that demonstrates the response to organizational changes that is taking place in many developed countries. It is associated with competency-determination, competency framework development, and using that competency framework as a basis for selecting, training, developing, and remunerating human resources. In Vietnam, through many years of administrative reform, though the quality of officials and civil servants have been improved, the results are modest. Therefore, the approach to civil servant management based on competency framework has been set. The project on job and/or position determination presided over by the Ministry of Home Affairs has initially approached the issues of developing competency framework for job and positions. However, the determination of competency framework for civil servants is still facing many difficulties because of the lack of systematic research and there’s no piloting of a complete sample competency framework (model) to be applied in practice in a specific sector or field in Vietnam. The author has practically studied the process of job/position determination of the Ministry of Home Affairs of Vietnam as a focal agency assigned by the Government of Vietnam to build regulations, implement and manage this mandate so far. In which, statistical data from the implementation results of the Project of job/position determination of the Ministry of Home Affairs are used.